(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, a hybrid image compression coding technique using the discrete cosine transform (DCT) and the discrete wavelet transform (DWT) is used for medical images. The aim is to achieve higher compression rates by applying different compression thresholds for LL and HH band wavelet coefficients. The DCT transform is applied on HL and LH bands with maintaining the quality of reconstructed images. After this, the image is quantized to calculate probability index for each unique quantity so as to find out the unique binary code for each unique symbol for their encoding